Effect of PCM on temperature fluctuation during the door opening of a household refrigerator. Issue 4 (16th March 2017) - Khan, Imran H.; Afroz, Hasan M. M.; Karim, M. A.
ABSTRACT: Temperature fluctuation inside the cabinet of a household refrigerator significantly affects the quality of preserved food. Phase change material (PCM) is a latent heat storage system that can store and release the heat energy by changing its phase from liquid to solid and solid to liquid respectively. Therefore, use of PCM inside the refrigerator cabinet has the potential for minimizing the temperature fluctuation during the door opening and the power failure. However, very few studies in the literature were dedicated to investigating the role of PCM to reduce the temperature fluctuation. The aim of this work is to experimentally investigate the effects of PCM on temperature fluctuation inside the cabinet of a household refrigerator during the door opening and power failure. The results found that a significantly lower temperature fluctuation can be obtained using PCM. It was found that during the door opening condition the air temperature in the cabinet rose rapidly. However, when a PCM container was used, temperature variation was reduced to 3–5°C. During the power failure, the system with PCM maintained a lower temperature inside the storage chamber for a long period of time (about 2 hours). Moreover, the test results indicate that PCM maintains more stable temperature in the foodstuffs inside the refrigerator. This reduction of temperature fluctuation ultimately improves the quality of preserved food.